Yield Loss Assessment and Management of Violet Wood Sorrel Weed on Maize (Nepal Agriculture Research Journal, 2014)
A field experiment was conducted during rainy season of 2003 and 2004 in farmers' field of Dang district (650 masl) to assess the yield loss caused by violet wood sorrel (Oxalis corymbosa Dc) for maize (Zea mays) and to work out effective measure to control this weed. Violet wood sorrel (Chari Amilo) infestation was observed in maize, ginger, and Toria fields of Dang and Salyan districts as well as various mid hilly areas of Nepal. The weed once introduced in uplands, spreads in large scale within few years. Six treatments, comprising 2,4-D Na salt 2 kg/ha, Glyphosate 2 l/ha, Soil digging, turning and expose to sun two months prior to maize sowing were compared with weed free, weed free except Oxalis and weedy check plots. The presence of violet wood sorrel (VWS) in maize field ranging from 38 to 352.3 per square meter in 2003 and 18.6 to 195.5 per square meter in 2004 one month after intercultural operation does not cause significant effect on maize grain yield, 4297 to 4694 kg/ha in 2003 and 3751.4 to 4473.6 kg/ha in 2004 respectively. Thus significant loss in maize grain yield was not found due to higher VWS weed population (352.3 and 195.5/m2) resulted in weedy check treatment and lower weed population (38 and 18.6/m2) in herbicide applied treatment. Repeated application of herbicides at 17 and 37 days after maize sowing (DAMS) both 2,4-D and Glyphosate reduced the weed population in maize field but could not eradicate as it appears in next year but the population was significantly low (59.5 and 65.3/m2) in herbicide applied plots compared to weedy check plot (322.6/m2) at 26 DAMS. It was revealed that presence of violet wood sorrel weed in maize field does not affect the grain yield in farmer's practice of weeding i.e. intercultural operation at 20 to 30 DAMS. Nepal Agric. Res. J. Vol. 8, 2007, pp. 38-41DOI: http://dx.doi.org/10.3126/narj.v8i0.11577